Analysis of marginal chipping of monolithic lithium disilicate crowns produced by four CAD-CAM systems - Strelhow, Samira Sandy Ferreira (2017)
Statement of the problem. The marginal integrity of monolithic crowns is an essential factor for longevity. Due to the wide application of CAD/CAM systems, evaluation of production accuracy is of great clinical interest. Purpose. Evaluating the marginal chipping of monolithic lithium disilicate crowns produced by four different CAD-CAM systems. Material and methods. Four CAD-CAM systems were selected: Ceramill (Ceramill Motion 2), Cerec (Cerec inLab MC XL), EDG (CAM5-S1 SmartDent) and Zirkonzahn (M5 Heavy). An artificial lower first molar was prepared for a full crown, duplicated in plaster, scanned and a crown was designed following standardized parameters. Ten lithium disilicate crowns (IPS e.max CAD) per group were milled. Images were obtained using a scanning stereomicroscope Stemi 2000-C (Zeiss), overlapped (Adobe Photoshop CS6 software) and measurents of the marginal perimeter and chipping area were performed (ImageJ software). To evaluate the degree of marginal chipping, the Chipping Factor (CF) of each crown was calculated and the data were subjected to Kruskal-Wallis One-way test followed by Dunns method (p< 0.05). Results. Based on SD and absolute mean values, the CF of Ceramill (14,5 ± 8,3) and Cerec (13,4 ± 9,4) groups was statistically higher than EDG (3,4 ± 1,2) and Zirkonzahn (2,8 ± 1,3). Conclusion. The data demonstrated the influence of selected parameters during the design, parameters settings and manufacturing tools of CAD/CAM systems on the marginal integrity of monolithic crowns.